Accountability and choice in schooling - Feintuck, Mike, 1961- (Law and political change., 1994)
The reform process in the schools system of England and Wales founded on the Education Reform Act 1988 promised that the introduction of competition would result in enhanced power and choice for parents which would, in turn, lead to increased accountability of those delivering education and a consequent improvement in educational standards. This book considers, both from a theoretical perspective and in light of empirical evidence, the extent to which these promises have been fulfilled.